Choragraphy Tubuh Nyai dalam Novel Mirah Dari Banda Karya Hanna Rambe: Kajian Politik Ruang Pascakolonial - Santoso, Joko (Balai Bahasa Jawa Barat, 2018)
This research examines how the representation of choragraphy of Nyai’s body in Hanna Rambe’s “Mirah dari Banda”. The theory used is the politics of Sara Upstone's postcolonial space that states that bodies and places are politically related to each other. The research uses a qualitative research method. The result of research reveals two findings. Firstly, there are choragraphy and ambiguity of self-meaning. There is no meaning or ideas on Nyai’s space and body. Secondly, there are choragraphy in space and body in between. The result of a cross between Nyai and his master is Indo-European children. Both conditions occur due to her Indo’s child in European-Dutch power.